Sejarah Pemikiran Muhammad Abduh dan Kontribusinya dalam Pendidikan Islam - Irfan Maulana Adnan (Education Research Center, 2025)
This study aims to examine the reformist ideas of Muhammad Abduh and his contributions to Islamic education. His thoughts emerged in response to the stagnation of Islamic education, which emphasized rote memorization and blind adherence (taqlid), limiting the development of critical and rational thinking. Through a rational and contextual approach, Abduh emphasized the importance of balancing intellect and spirituality. He redefined educational goals to include both worldly success and spiritual fulfillment, proposed a tiered curriculum from elementary to higher education, and encouraged teaching methods that stimulate conceptual understanding and critical thinking. This study employs a descriptive qualitative method based on library research. The findings indicate that Abduh's vision especially regarding the integration of religious and secular sciences, curriculum reform, and the revival of ijtihad is highly relevant to contemporary Islamic education. His reformist spirit and emphasis on intellectual freedom offer a solid foundation for transforming Islamic education into a more balanced, rational, and contextual system that aligns with modern challenges.